Challenges, Legal Aperture and Future Approaches in Handling Sexual Offence Cases in India: A Comprehensive Review - Chouhan, Avinash; M Ratadiya, Prashant; Parekh, Utsav; Gupta, Sanjay (Journal of Forensic Medicine and Toxicology, 2026)
The cases of sexual offence remain a serious medico-legal and social problem in India. According to the National Crime  Records Bureau, more than 31,000 rape incidents were recorded in 2022, a figure which has gone up from around 25,000  in 2012, showing an inexorable rise despite numerous reforms since the 2012 Delhi gang-rape case. An incident that  happened in 2024, the Kolkata doctor’s sexual assault and murder have once again triggered public outrage due to systemic lapses related to forensic evidence collection, police investigation, and survivor care. The review identifies recur ring gaps, including forensic inadequacies, chain-of-custody breaches, medico-legal documentation failures, and judicial  delays, which are made worse by societal apathy and a growing link between sexual violence and pornography addiction.  Despite legislative efforts conviction rates remain under 30% due to laboratory backlogs and deficits within the proce dure. This review concludes with proposed reforms expanding forensic laboratories, carrying out standardized protocols  for evidence handling, integrating models of forensic nursing and tele-forensic, and providing trauma-informed survivor  Centered care. Strengthening these medico-legal and forensic mechanisms is very essential for increasing the conviction  rate and restoring confidence among the general public and dignity among survivors.
Keywords: Forensic capacity; Sexual offences; Tele-forensics; Forensic nursing; Survivor centered justice